Postsynaptic Rab GTPases and Exocyst: a screen at the Drosophila neuromuscular junction - Patrício-rodrigues, Cátia (2021)
Funding:This work was supported by H2020-GA661543-Neuronal Trafficking (ROT), IF/00392/2013/ CP1192/CT0002, FCT – Portugal (ROT) and by UID/Multi/04462/2013 from iNOVA4Health (co-fundend by FCT-FEDER-PT2020).